2002
DOI: 10.1016/s0896-6273(02)00671-2
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Dependent Synaptotagmin Binding to SNAP-25 Is Essential for Ca2+-Triggered Exocytosis

Abstract: Synaptotagmin is a proposed Ca2+ sensor on the vesicle for regulated exocytosis and exhibits Ca2+-dependent binding to phospholipids, syntaxin, and SNAP-25 in vitro, but the mechanism by which Ca2+ triggers membrane fusion is uncertain. Previous studies suggested that SNAP-25 plays a role in the Ca2+ regulation of secretion. We found that synaptotagmins I and IX associate with SNAP-25 during Ca2+-dependent exocytosis in PC12 cells, and we identified C-terminal amino acids in SNAP-25 (Asp179, Asp186, Asp193) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
216
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 66 publications
13
216
0
1
Order By: Relevance
“…Third, the short linker between the two C2 domains would limit the orientations that the C2A domain can adopt, enhancing the rapid response to the calcium signal. In this orientation, C2A may respond to calcium entry either through binding electrostatically to the phospholipid membrane (Fernandez-Chacon et al, 2001) or, as has also been suggested, through the inducible, calcium-dependent, binding to SNAREs (Zhang et al, 2002;Bai et al, 2004). This inducible SYT/SNARE interaction exhibits properties very different from those characteristic of the constitutive association.…”
Section: Discussionmentioning
confidence: 89%
“…Third, the short linker between the two C2 domains would limit the orientations that the C2A domain can adopt, enhancing the rapid response to the calcium signal. In this orientation, C2A may respond to calcium entry either through binding electrostatically to the phospholipid membrane (Fernandez-Chacon et al, 2001) or, as has also been suggested, through the inducible, calcium-dependent, binding to SNAREs (Zhang et al, 2002;Bai et al, 2004). This inducible SYT/SNARE interaction exhibits properties very different from those characteristic of the constitutive association.…”
Section: Discussionmentioning
confidence: 89%
“…refs. 40,42,54 ), yet there were contradictory data on these interactions and it was unclear how they might be coupled with Ca 2+ -phospholipid binding to synaptotagmin 1. The results described here now shed light on these questions, showing that synaptotagmin 1 forms an intimate quaternary complex with the SNAREs, Ca 2+ and phospholipids, and suggesting that membrane-anchoring of SNARE complexes increases the specificity of their interactions with synaptotagmin 1.…”
Section: Discussionmentioning
confidence: 99%
“…refs. [36][37][38][39][40]. Moreover, synaptotagmin 1 and the SNAREs are sticky proteins that have been reported to bind to many different targets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence that synaptotagmin-1 binds to the SNARE complex or to individual SNAREs through interactions with one or both C2-domains (Bennett et al, 1992;Sollner et al, 1993;Chapman et al, 1995;Schiavo et al, 1997;Zhang et al, 2002;Rickman and Davletov, 2003;Shin et al, 2003;Bai et al, 2004;Bhalla et al, 2006;Pang et al, 2006;Lynch et al, 2007). It is possible that the SNAP-25 linker participates in synaptotagmin binding in situ.…”
Section: Discussionmentioning
confidence: 99%